The Effect of Product Quality, Price, and Store Atmosphere on Purchase Decision - Kurniawan, Muhammad Akbar; Maharani, Nabila Putri (Manunggal Halim Jaya, 2026)
This study aims to determine the effect of product quality, price, and store atmosphere on consumer purchasing decisions at Nuju Coffee in Bandar Lampung. The method used in this study is a quantitative approach with data collection through questionnaires and analyzed using multiple linear regression. This study involved Nuju Coffee customers as respondents. The results showed that product quality, price, and store atmosphere significantly influence consumer purchasing decisions. Simultaneously, these three variables contribute to consumer decisions when buying products at Nuju Coffee. This study concludes that product quality, competitive prices, and a comfortable store atmosphere drive customer purchasing decisions in the coffee shop industry.